Corporate Social Responsibility as a Moderator of the Relationship Between Good Corporate Governance and Firm Value - Aini, Nurul; Pirmaningsih, Lilik; Pradika, Novaldy Arief; Amalia, Afina; Oktaviani, Maya (Program Pascasarjana Universitas Negeri Makassar, 2025)
This study aims to examine and analyze the moderating role of Corporate Social Responsibility (CSR) in the relationship between Good Corporate Governance (GCG) and firm value. Good Corporate Governance in this context is proxied by managerial ownership, institutional ownership, and the proportion of independent commissioners. The research employs a sample of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period, resulting in a final sample of 66 firm-years. Data were analyzed using SPSS software. The findings reveal that, partially, managerial ownership, institutional ownership, and independent commissioners have a significant positive effect on firm value. Furthermore, the moderation analysis indicates that Corporate Social Responsibility moderates the effect of managerial ownership on firm value. However, CSR does not moderate the relationship between institutional ownership or independent commissioners and firm value.